E-Learning Interaktif dalam Pembelajaran Matematika Ekonomi dengan Menggunakan Aplikasi Blender - Lia Asmalah; Angga Hidayat (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2020)
This research was conducted in order to measure how far the influence of the use of the blender application as a synchronous medium in the implementation of e-learning at Pamulang University in particular to increase distance learning motivation in learning economic mathematics. This study uses a research and development research type and a instructional design model of instructional design. The subjects in this study were learning media on the subject of economic mathematics at Pamulang University. The assessment score given by 500 Pamulang University students as respondents, became the data which was then analyzed by validity testing with the product moment correlation technique, and reliability testing using the Croanbach alpha technique. The results of the analysis show that for the validity of the assessment score given by the Respondent to the learning media of economic mathematics subject is greater than r tabek, while the reliability of the respondent's assessment score on the learning media of economic mathematics subject has a Cronbach alpha value greater than 0.7. Based on the data above, the researcher concludes that the learning media for the subject of economic mathematics using the opensources blender application are declared valid and reliable so that it can be said to be feasible to be used as a learning medium to increase distance learning motivation at Pamulang University